Revision of the Neotropical ladybird genus Parinesa Gordon (Coleoptera, Coccinellidae) - Escalona, Hermes E.; Ślipiński, Adam (Zootaxa, 2012)
The genus Parinesa Gordon is revised, differentiated from the genera Argentipilosa Gordon & Almeida and GlomerellaGordon and placed in Argentipilosini (Coccinellinae), the genus was previously known by one species from The GreaterAntilles. Ten species are recognized in Parinesa: P. whiteheadi Gordon, 1991 (type species), P. gnoma (Gordon, 1977) n.comb. transferred from Glomerella and the new species P. bechynorum sp. nov. and P. carioca sp. nov. from Brazil; P.minuta sp. nov. from Panama and P. ariasi sp. nov., P. jolyi sp. nov., P. lemae sp. nov., P. saviniae sp. nov. and P. anae sp. nov. from Venezuela.